CORPORATE GOVERNANCE DAN FAKTOR LAINNYA: APAKAH MEMENGARUHI FIRM VALUE - DARREN HANSEL; RUDI SETIADI TJAHJONO (E-Jurnal Manajemen Trisakti School of Management (TSM), 2026)
This study aims to obtain empirical evidence regarding the influence of various independent variables on the dependent variable, namely firm value, as measured by Price Book Value (PBV). The objects of this research are all manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2022 to 2024. The number of samples that met the criteria in this study is 126 manufacturing companies, with a total of 378 data. The samples were selected using a purposive sampling method and analyzed using multiple linear regression. The results of this study indicate that independent commissioners, capital structure, and profitability have a positive effect on firm value. In addition, the audit committee, earnings management, activity ratio, firm size, and liquidity are found to have no effect on firm value.